Editor's note - Antić, Ana (Medical Word, 2021)
The SARS CoV-2 virus pandemic is a global and unexpected threat that has hit all spheres of life and stopped the whole world. The rapid spread of the virus has caused reduced movements, social distancing, and cancellation of numerous scientific and professional gatherings that had been planned long in advance. One of them is the XIV Congress of the National Association of Health Workers of Serbia, which was planned for the period between 20th and 24th  of May 2020, and then for the period between 1st and 5th of July 2020. Due to the inconvenient epidemiological situation, congress was not held. Considering that doctors, nurses, and all health workers are on the frontline against the COVID-19 infection, the Editorial Board of the journal “Medical word” decided to thank them and support them by printing this issue of the journal which is a collection of abstracts submitted for the XIV Congress of the National Association of Health Workers of Serbia. While we are struggling with the greatest health challenge in this century, we want to thank all our colleagues who previously prepared their work for this professional gathering and their dedication and selfless commitment to performing their regular and now additional duties. We also want to thank them for taking care of the health and safety of patients on a daily basis.In the hope of returning to regular life and work activities and obligations as soon as possible, we invite our colleagues to send their professional papers for the upcoming issues of the journal. Already with the first issue, “Medical word” was extremely well-received by the scientific and general public, which gives us a strong motivation for further work.